HIV testing and its associated factors among street-based female sex workers in Iran: results of a national rapid assessment and response survey - Sina Ahmadi; Mehrdad Khezri; Payam Roshanfekr; Salah Eddin Karimi; Meroe Vameghi; Delaram Ali; Elahe Ahounbar; Mehdi Noroozi; Mostafa Shokoohi (BMC, 2021)
Abstract Background Female sex workers (FSWs) are at a disproportionate risk of sexually transmitted infections and they may face significant barriers to HIV testing. This study aimed to examine HIV testing prevalence and its associated factors among street-based FSWs in Iran. Method A total of 898 FSWs were recruited from 414 venues across 19 major cities in Iran between October 2016 and March 2017. Eligible FSWs were women aged 18 years of age who had at least one commercial sexual intercourse in the previous year. HIV testing was defined as having tested for HIV in the lifetime. Bivariable and multivariable logistic regression were used to examine the correlates of HIV testing. We report adjusted odds ratios (aOR) and their 95% confidence intervals (CI). Result Overall, 57.8% (95%CI: 20.0, 88.0) of participants reported having tested for HIV, and HIV prevalence among FSWs who tested for HIV was 10.3% (95%CI: 7.5, 13.0). The multivariable model showed that unstable housing (aOR: 8.86, 95%CI: 2.68, 29.32) and drug use (aOR: 3.47, 95%CI: 1.33, 9.06) were associated with increased likelihood of HIV testing. However, FSWs with a higher level of income were less likely to be tested for HIV (aOR: 0.09, 95%CI: 0.02, 0.43). Conclusion Almost one in ten street-based FSWs had never tested for HIV. These findings suggest the need for evidence-based strategies such as outreach support and HIV self-testing to improve HIV testing in this marginalized population.